Aktivitas Penghambatan Xantin Oksidase pada Ekstrak Daun Sirih Hitam (Piper sp) - Muhammad Amir Masruhim; Wisnu Cahyo Prabowo; Dita Paramitha (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2016)
Hyperuricemia is a condition in which increased levels of uric acid in the blood. Xanthine oxidase role in the oxidation of hypoxanthine and xanthine to uric acid. One treatment of hyperuricemia is inhibiting xanthine oxidase in the process of formation of uric acid. The purpose of this study to determine the inhibitory activity of xanthine oxidase in the ethanol extract of black betel leaf (Piper sp). Xanthine oxidase inhibitory activity test using UV-Vis spectrophotometry in vitro with a concentration of 5 ppm, 10 ppm and 20 ppm. The data obtained were analyzed using one-way ANOVA. The result is the ethanol extract of black betel leaf has a different activity significantly and IC50 values obtained is 65.96 ppm.